2017
DOI: 10.1016/j.ijscr.2017.08.037
|View full text |Cite
|
Sign up to set email alerts
|

A rare case report of patent vitellointestinal duct causing bowel obstruction in an adult

Abstract: HighlightsPatent vitellointestinal duct is very rare congenital condition.We report an unusual case of patent vitellointestinal duct causing intestinal obstruction in adult patient.Awareness of this a rare cause of bowel obstruction is important for appropriate management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Despite careful attention during laparoscopic surgery is needed, iatrogenic intestinal harm may occur more frequently than with an open procedure due to limited working area and dilated weak intestinal loops. 5,15 VI duct remnants usually contain heterotopic mucosa that can cause complications in our case there was evidence of gastric mucosa that may lead to ulceration and intestinal bleeding. This is why we prefer complete excision of the VI duct and be sure that no other residual tissue remains not only to be presented by benign nature bleeding but also it was reported before to be presented by malignant neoplasm.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Despite careful attention during laparoscopic surgery is needed, iatrogenic intestinal harm may occur more frequently than with an open procedure due to limited working area and dilated weak intestinal loops. 5,15 VI duct remnants usually contain heterotopic mucosa that can cause complications in our case there was evidence of gastric mucosa that may lead to ulceration and intestinal bleeding. This is why we prefer complete excision of the VI duct and be sure that no other residual tissue remains not only to be presented by benign nature bleeding but also it was reported before to be presented by malignant neoplasm.…”
Section: Discussionmentioning
confidence: 48%
“…14 Presentation of VI duct remnant in adults varies between Abdominal pain, rectal bleeding, umbilical hernia and intestinal obstruction, enteric fistula, Meckel's diverticulum, vitelline cord, umbilical granuloma or umbilical sinus. 4,5 In this case report, our patient complained of a long history of on-and-off abdominal pain that was colicky in nature, particularly with fast food. Such a case with a virgin abdomen and intermittent abdominal pain warrants further investigation to detect the VI pathology and treat it electively rather than waiting for the patient to present in an emergency situation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It was caused by the volvulus of the small-bowel around the diverticular axis. The frequency of intestinal obstruction due to a fibrous band of the vitelline duct as in our first case is very rare ( 11 ). However, if the diagnosis and surgical treatment are delayed, the intestines might become gangrenous and the intestinal resection is unavoidable ( 11 ).…”
Section: Discussionmentioning
confidence: 61%
“…In 2015, Rekhi et al [6] reported a case in which a 1-yearold child presented with paraumbilical abscess who had underwent incision and drainage twice for the same but later on found to have patent VID on laparotomy. Small-bowel obstruction due to persistent VID, particularly in adult patients, is rare with very few case reports in world literature [4,7]. Patent VID leading to paraumbilical abscess which further led to intestinal obstruction in an adult has not been reported earlier to the best of our knowledge.…”
Section: Discussionmentioning
confidence: 99%